2018
DOI: 10.1002/jcop.22136
|View full text |Cite
|
Sign up to set email alerts
|

Queering Black activism: Exploring the relationship between racial identity and Black activist orientation among Black LGBTQ youth

Abstract: Linked fate, or connection to the Black community, may be a pathway to engagement in social justice action for Black liberation. The purpose of this study is to understand the role of racial identity on Black queer youths’ orientation toward Black activism. We used hierarchical linear regression to examine relationships between dimensions of racial identity and Black activism orientation among 142 queer‐identified youth. We found that racial centrality and racial ideologies predicted high‐risk activism orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…There is a growing literature examining the motivations and barriers to activism in samples of predominantly white LGBTQ+ individuals (Breslow et al, 2015; Craney, Watson, Brownfield, & Flores, 2018; Dunn & Szymanski, 2018; Friedman & Leaper, 2010; Swank, 2018; Swank & Fahs, 2012, 2013, 2019; Swank, & Fahs, B., 2016), as well as a number of studies examining the impact of intersectional experiences of oppression on participation in activism for LGBTQ+ black, Indigenous and people of colour (BIPOC; Battle & Harris, 2013a, 2013b; DeBlaere et al, 2014; Harris & Battle, 2013; Harris, Battle, Pastrana Jr, & Daniels, 2013; Harris, Battle, Pastrana, & Daniels, 2015; Pender, Hope, & Riddick, 2019; VanDaalen & Santos, 2017; Santos & VanDaalen, 2018). With regard to research with LGBTQ+ BIPOC samples, findings show a number of predictors for participation in activism.…”
Section: Motivations and Barriers To Lgbtq+ Activist Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing literature examining the motivations and barriers to activism in samples of predominantly white LGBTQ+ individuals (Breslow et al, 2015; Craney, Watson, Brownfield, & Flores, 2018; Dunn & Szymanski, 2018; Friedman & Leaper, 2010; Swank, 2018; Swank & Fahs, 2012, 2013, 2019; Swank, & Fahs, B., 2016), as well as a number of studies examining the impact of intersectional experiences of oppression on participation in activism for LGBTQ+ black, Indigenous and people of colour (BIPOC; Battle & Harris, 2013a, 2013b; DeBlaere et al, 2014; Harris & Battle, 2013; Harris, Battle, Pastrana Jr, & Daniels, 2013; Harris, Battle, Pastrana, & Daniels, 2015; Pender, Hope, & Riddick, 2019; VanDaalen & Santos, 2017; Santos & VanDaalen, 2018). With regard to research with LGBTQ+ BIPOC samples, findings show a number of predictors for participation in activism.…”
Section: Motivations and Barriers To Lgbtq+ Activist Participationmentioning
confidence: 99%
“…For example, VanDaalen and Santos (2017) found that a higher perception of racism in the queer community was associated with great sociopolitical involvement in both queer and BIPOC communities for LGBTQ+ BIPOC participants. Additionally, Pender et al (2019) found that for queer black youth (ages 13–29), the centrality of race to their self‐concept correlated with their intent to participate in black activism. Other studies have found connection to LGBTQ+ community to be a motivation for activism for various BIPOC samples (Battle & Harris, 2013a, 2013b; Harris et al, 2015; Harris & Battle, 2013).…”
Section: Motivations and Barriers To Lgbtq+ Activist Participationmentioning
confidence: 99%
“…Also, action involves marches, talking to the community, promoting other people to follow your beliefs, transmitting ideas to people who don't have the same vocabulary. (Welton et al, 2017, p. 89) Fundamentally, activism is often a grassroots effort directed toward changing political processes and procedures (Pender et al, 2019). More specifically, youth and/or student activism commonly involves young people collectively taking action to challenge and hopefully change racial injustices in policy (Mitra et al, 2013).…”
Section: Activismmentioning
confidence: 99%
“…At the individual level, an activist is a person who "is known for taking stands and engaging in action aimed at producing social change" (Marshall & Anderson, 2008, p.18); and an individual's decision to participate in activism can be influenced by an activists' collective and/or a larger social movement (Horowitz, 2017). Moreover, an individual's decision to initiate or participate in activism can also be based on their identity, whether it be a shared political cause, grievance or injustice; or associations along race, class, (dis)ability, gender identity, sexuality, language, immigration status, and any intersections of these identities for which they are minoritized and seek structural retribution as a result (Horowitz, 2017;Pender et al, 2019).…”
Section: Activismmentioning
confidence: 99%
See 1 more Smart Citation